Numerical Method for a Markov-Modulated Risk Model with Two-Sided Jumps - Hua Dong; Xianghua Zhao (Abstract and Applied Analysis)
This paper considers a perturbed Markov-modulated risk model with two-sided jumps, where both the upward and downward jumps follow arbitrary distribution. We first derive a system of differential equations for the Gerber-Shiu function. Furthermore, a numerical result is given based on Chebyshev polynomial approximation. Finally, an example is provided to illustrate the method.